Forms of Indigenous Labor on New Spain’s Northern Frontiers: The Cases of New Mexico and California (17th–18th Centuries) - David Rex Galindo (Rechtsgeschichte - Legal History)
This essay discusses various forms of Hispanic-Indigenous labor relations on New Spain’s northern frontiers, with a focus on 17th-century New Mexico and late colonial California. The article reconstructs how local practices of exploitation and abuse took various forms and eventually acquired normative values. In doing so, it offers an analysis of the interconnectivity of practices and norms in labor relations in such frontier territories. The essay takes historical, normative, and etymological approaches to reveal the diversity of labor systems and forms of coercion then present in New Mexico and California as well as the various conceptual and normative foundations behind this plethora of systems.